Desenvolvimento de uma camada nitretada em aço inoxidável martensítico para aplicação em anéis de pistão, quando utilizada em motores ciclo otto bi-combustíveis (motores flex-fuel) - Nocera, Eduardo (2013)
Piston rings are metal parts which, when installed on the pistons in the cylinders of the engine, become circular with variable pressure and self-expansive, providing a movable seal between the combustion chamber and the crankcase. These components are subjected to intense functional demand, being asked to submit a low wear rate and maintain their structural and functional integrity under high temperatures and pressures. Due to these requirements, the technique is known of providing up-to-face contact with coatings or surface treatments to improve wear. Currently the majority of applications in the compression rings are martensitic stainless steels. These rings have their tribological properties improved by gas nitriding treatment which gives the steel surface intermediate properties between metallic and ceramic materials with high resistance to adhesive wear, as well as to wear by abrasion. This technology has been applied since the 90s with great success and high market penetration. With demand growing for reducing emissions was introduced in the market the Otto cycle engines with bifuel, better known as Flex engines. The principle of operation of these engines is the use of gasoline and ethanol at any mixing. The compression ratio of the piston is optimized for gasoline and not optimized for ethanol, since the latter does not have limitations to the phenomenon of detonation and this fact makes it occurs more Ethanol injection into the combustion chamber providing an improper fuel does not wash burnt in the cylinder wall. The result was the creation of a different tribological system in the area of operation of the rings where the nitrided layer began to suffer a detachment. This study aimed to find a solution for this detachment, where the nitride layer was changed. The modification consisted in decreasing the precipitation of carbides in the grain boundaries through migration carbon more to the core of the ring making it more robust to cracks and less susceptible to hydrogen embrittlement. Was created two nitriding stages, one richer in nitrogen which provides the wear resistance required for applying and the second stage causes the carbon to become more concentrated in the core hindering the generation of cracks and, consequently, the detachment. There was a decrease in the hardness of the nitrided layer without deteriorating the wear resistance, creating a unique solution and extending the life of this technology.